The Influence Of Product Quality, Service Quality, And Price On Purchasing Decisions Through Consumer Beliefs As a Variable Intervening At Pt. Freya Frist Indonusa Medan - Nasution, Rizki Fajri; Lubis, Adelina; Aisyah, Nur (UNIVERSITAS PAKUAN, 2025)
This study aims to analyze the influence of product quality, service quality, and price on purchase decisions, with consumer trust acting as an intervening variable at PT. Freya Frist Indonusa Medan. The independent variables in this study include Product Quality (X1), Service Quality (X2), and Price (X3), while the dependent variable is Purchase Decision (Y), with Consumer Trust (Z) as the mediating factor. A quantitative approach is employed, utilizing data collection techniques such as questionnaires and direct observations to gather responses from consumers. The study population comprises 225 consumers, and by applying Slovin’s formula with a significance level of 0.05, a representative sample of 144 respondents was selected. The collected data is then analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method, facilitated by SmartPLS software, to examine the relationships between variables and test the proposed hypotheses. The findings reveal that Product Quality (X1) has a significant positive effect on Consumer Trust (Z), indicating that higher product quality enhances consumer confidence in the brand. Similarly, Service Quality (X2) also positively influences Consumer Trust (Z), suggesting that superior service contributes to higher levels of trust. Additionally, Price (X3) positively impacts Purchase Decision (Y), showing that competitive pricing strategies influence consumer choices. These results highlight the importance of maintaining high product and service quality while setting reasonable prices to strengthen consumer trust, ultimately leading to better purchase decisions and increased customer satisfaction at PT. Freya Frist Indonusa Medan.